An agent-based self-configuration methodology for modular assembly systems - Ferreira, Pedro (2011)
Assembly systems today are exposed to market trends that have become increasingly more dynamic and unpredictable, requiring product changes and adjustments which emphasise de need for more flexible systems. The requirement for increased responsiveness has led to the development of new modular concepts which provide the bases for achieving higher system adaptability through increased component/module interchangeability and reusability. The modularization of physical and control infrastructure does, however, only address one aspect of the issue and there is still a lack of appropriate tools and methods to support the rapid configuration and reconfiguration of such systems for changing sets of requirements.